The success of IS/IT co-sourcing contract arrangements in government agencies - Edguer, Erhan; Pervan, Graham (Southern Cross University, 2001)
The main objective of this research was to explore how critical success factors affected the outsourcingarrangements between buyers and suppliers in small government organizations, which collectively outsource their IS/IT activities to a single outsourcing vendor. A major finding of this study was that organizations could have a successful co-sourcing arrangement by determining and putting into practice certain critical success factors. In this regard, it can contribute to the existing body of knowledge in co-sourcing activities that have been growing rapidly in government departments as well as in the private sector.